Global existence of solutions of a semilinear heat equation with nonlinear memory condition. Issue 16 (9th December 2020) - Gladkov, Alexander; Guedda, Mohammed
Abstract : We consider a semilinear parabolic equation with flux at the boundary governed by a nonlinear memory. We give some conditions for this problem which guarantee global existence of solutions as well as blow-up in finite time of all nontrivial solutions. The results depend on the behavior of variable coefficients as t → ∞ .